1996
DOI: 10.1073/pnas.93.20.11035
|View full text |Cite
|
Sign up to set email alerts
|

Local stress, not systemic factors, regulate gene expression of the cardiac renin-angiotensin system in vivo: a comprehensive study of all its components in the dog.

Abstract: Local stress, not systemic factors, regulate gene expression of the cardiac renin-angiotensin system in vivo: A comprehensive study of all its components in the dog (heart/heart hypertrophy/gene regulation/heart failure) YOUNG-AE LEE*, CHANG-SENG LIANGt, MIN The renin-angiotensin system (RAS) contributes importantly to the maintenance of acute and chronic hemodynamic homeostasis by affecting the function as well as the structure of the cardiovascular system. In addition to the classically described endocrine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 43 publications
4
29
0
2
Order By: Relevance
“…75,76 Fibrosis is also triggered by atrial dilation in any type of heart disease associated with AF, including valvular disease, hypertension, HF, or coronary atherosclerosis. 77 Stretch activates several molecular pathways, including the renin-angiotensin-aldosterone system (RAAS). Both angiotensin II and transforming growth factor-beta1 (TGF-beta1) are upregulated in response to stretch, and these molecules induce production of connective tissue growth factor (CTGF).…”
Section: Atrial Pathology As a Cause Of Atrial Fibrillationmentioning
confidence: 99%
“…75,76 Fibrosis is also triggered by atrial dilation in any type of heart disease associated with AF, including valvular disease, hypertension, HF, or coronary atherosclerosis. 77 Stretch activates several molecular pathways, including the renin-angiotensin-aldosterone system (RAAS). Both angiotensin II and transforming growth factor-beta1 (TGF-beta1) are upregulated in response to stretch, and these molecules induce production of connective tissue growth factor (CTGF).…”
Section: Atrial Pathology As a Cause Of Atrial Fibrillationmentioning
confidence: 99%
“…Responses to applied or intrinsic mechanical forces have been studied in many cell types. Well-established stretch-mediated responses include gene expression regulation (39), cell proliferation ( 48 ), and peptide growth factor induction (25,46). Using a static stretch system, van Wamel et al (46) showed that stretch could cause neonatal CFb to release TGF-␤1.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided both in vitro and in vivo that mechanical forces can selectively regulate gene expression and cause differential induction of peptide growth factors. [27][28][29] The augmented formation of IGF-I and ET-1 depends on the increased left ventricle load and is not related to possible derangements of pulmonary or peripheral hemodynamics, because no evidence of enhanced cardiac growth factor formation was found in patients with mitral stenosis despite the presence of atrial fibrillation, enhanced pulmonary arterial pressure, and increased levels of circulating ET-1 and Big ET. Likewise, the occurrence of stable effort angina in the formation of ET-1 and IGF-I seems to play a minor role, given that no significant differences were found between patients with and patients without angina and coronary artery disease.…”
Section: Compensatory Hypertrophy and Selective Formation Of Growth Fmentioning
confidence: 99%